The present profile of chronic hepatitis B virus infection highlights future challenges: An analysis of the Multicenter Italian MASTER-B cohort. Issue 3 (March 2019) - Brancaccio, Giuseppina; Nardi, Alessandra; Madonia, Salvatore; Fasano, Massimo; Verucchi, Gabriella; Massari, Marco; Maimone, Sergio; Contini, Carlo; Levantesi, Fabio; Alfieri, Arianna; Gavrila, Caius; Andreone, Pietro; et al.
Abstract: Background: Chronic hepatitis B virus (HBV) infection remains a primary cause of morbidity and mortality worldwide. Aim: The study is aimed at updating the clinical and epidemiological profile of chronic HBV infection in Italy. Methods: A cross-sectional multicenter prospective study enrolled consecutive HBsAg positive patients seen in 73 Italian centers in the period 2012–2015. Individual patient data were collected using an electronic platform and analyzed using standard statistical methods. Results: Among 2877 HBsAg positive individuals (median age 49.8 years, 68% males), 27% were non-Italian natives (NINs); 20% had chronic infection, 58.5% chronic hepatitis and 21.5% cirrhosis. Among NINs, age was younger, male gender was less prevalent and liver disease less advanced than in Italians (all p < 0.0001). HBeAg positive cases were 23.6% among NINs vs 8.2% in Italians (p < 0.0001); HDV coinfections 11.1% vs 7.3% (p = 0.006) and HCV coinfections 2.3% vs 4.2% (p = 0.017), respectively. Anti-HDV or anti-HCV antibodies were detected more frequently in patients with cirrhosis. Fifty percent of NINs with cirrhosis were aged below 45 years. Conclusion: The study offers an insight into the evolving burden of chronic hepatitis B virus infection in the near future and highlights new territories for public health interventions.